Advertising and disclosure of funding on patient organisation websites: a cross-sectional survey - Tisocki Klara; Ball Douglas E; Herxheimer Andrew (BMC, 2006)
Abstract Background Patient organisations may be exposed to conflicts of interest and undue influence through pharmaceutical industry (Pharma) donations. We examined advertising and disclosure of financial support by pharmaceutical companies on the websites of major patient organisations. Method Sixty-nine national and international patient organisations covering 10 disease states were identified using a defined Google search strategy. These were assessed for indicators of transparency, advertising, and disclosure of Pharma funding using an abstraction tool and inspection of annual reports. Data were analysed by simple tally, with medians calculated for financial data. Results Patient organisations websites were clear about their identity, target audience and intention but only a third were clear on how they derived their funds. Only 4/69 websites stated advertising and conflict of interest policies. Advertising was generally absent. 54% of sites included an annual report, but financial reporting and disclosure of donors varied substantially. Corporate donations were itemised in only 7/37 reports and none gave enough information to show the proportion of funding from Pharma. 45% of organisations declared Pharma funding on their website but the annual reports named more Pharma donors than did the websites (median 6 vs. 1). One third of websites showed one or more company logos and/or had links to Pharma websites. Pharma companies' introductions were present on 10% of websites, some of them mentioning specific products. Two patient organisations had obvious close ties to Pharma. Conclusion Patient organisation websites do not provide enough information for visitors to assess whether a conflict of interest with Pharma exists. While advertising of products is generally absent, display of logos and corporate advertisements is relatively common. Display of clear editorial and advertising policies and disclosure of the nature and degree of corporate donations is needed on patient organisations' websites. An ethical code to guide patient organisations and their staff members on how to collaborate with Pharma is also necessary, if patient organisations are to remain independent and truly represent the interests and views of patients. As many organizations rely on Pharma donations, self-regulation may not suffice and independent oversight bodies should take the lead in requiring this.